VIDEOFLUOROSCOPIC SWALLOWING STUDY: esophageal alterations in patients with dysphagia - SCHEEREN,Betina (2014)
Context Videofluoroscopic swallowing study is a dynamic exam and allows the evaluation of the complete swallowing process. However, most published studies have only reported alterations in the oropharynx and pharyngoesophageal transition, leaving the analysis of the esophagus as a secondary goal. Objectives The goal of this study was to investigate the prevalence of alterations in the esophageal phase thorough videofluoroscopic swallowing study in patients with dysphagia. Methods Consecutive patients with dysphagia who underwent videofluoroscopic swallowing study including esophageal analysis between May 2010 and May 2012 had their exams retrospectively reviewed. Patients were classified into two groups: Group I - without a pre-established etiological diagnosis and Group II - with neurological disease. During the exam, the patients ingested three different consistencies of food (liquid, pasty and solid) contrasted with barium sulfate and 19 items were analyzed according to a protocol. The esophageal phase was considered abnormal when one of the evaluated items was compromised. Results Three hundred and thirty-three (n = 333) consecutive patients were studied - 213 (64%) in Group I and 120 (36%) in Group II. Esophageal alterations were found in 104 (31%) patients, with a higher prevalence in Group I (36.2%), especially on the items esophageal clearance (16.9%) and tertiary contractions (16.4%). It was observed that 12% of individuals in Group I only presented alterations on the esophageal phase. Conclusion Evaluation of the esophageal phase of swallowing during videofluoroscopic swallowing study detects abnormalities in patients with cervical dysphagia, especially in the group without pre-established etiological diagnosis.